Report of the Steering Group on Science and Technology and Environment for the Seventh Five Year Plan (1985-90) - Planning Commission (Planning Commission, 1984)
Before Independence, between 1900-1950 the Indian economy basically languished, with national income growing at 1.3%, agriculture at 0.1% and industrial production at 2.7%. Over the past three decades, since planning of the Indian economy started, there has been an overall real growth around 4%, with a growth rate of about 2.3% in agriculture, and of 5-6% in industry.
Planning Commission Government of India
Planning Commission Government of India